Beyond Redistribution: In‐Stream Habitat Restoration Increases Capacity for Young‐of‐the‐Year Chinook Salmon and Steelhead in the Entiat River, Washington. (13th April 2020) - Polivka, Carlos M.; Claeson, Shannon M.
Abstract: We conducted snorkel surveys for juvenile salmonids in reaches of the Entiat River, Washington, treated with engineered logjams and in reaches without treatments to determine if observations at a habitat unit scale can identify whether restoration has increased the habitat capacity of a reach. The conceptual basis and field methodology emphasize fish density data (fish/habitat area in m 2 ) from unrestored habitat within a reach treated with engineered logjams compared with surveys in (1) unrestored habitat in untreated reaches and (2) restored habitat in treated reaches. A Bayesian generalized linear model enabled us to quantify density differences among habitat types using advanced computational statistics. Modal density of young‐of‐the‐year Chinook Salmon Oncorhynchus tshawytscha and steelhead O. mykiss was at least 3.1‐fold and 2.7‐fold greater, respectively, in restored habitat compared with unrestored habitat for all treated reaches examined. To distinguish the density differences in those reaches as capacity increases rather than redistribution from poor habitat to good habitat, we compared density in unrestored habitat in both treated and untreated reaches. Here we found no differences for either species, confirming that the increased density in restored habitat units did not come from depletion of unrestored habitat in the same reach. We thus concluded that restoration increased the habitat capacity of the reach at the scale of pools created by engineered logjams.